Peran Guru Pendidikan Pancasila dan Kewarganegaraan dalam Menanamkan Civic Disposition Bagi Peserta Didik - Asli Sadar Hati Lahagu; Amstrong Harefa; Fatiani Lase; Berkat Persada Lase (Pusat Riset dan Inovasi Nasional, 2024)
Civic disposition is an important aspect of civic education, because it functions to shape the character of students who are responsible, tolerant, and active in democratic life. This study aims to describe and analyze the role of school principals, Civics teachers in instilling civic disposition to students at UPTD SMP Negeri 1 Mandrehe Utara. Using a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews. Using thematic analysis techniques to explore various information from related parties in the schools studied. The results showed that Civics teachers have a strategic role in instilling civic disposition through active learning approaches, providing role models, and integrating civic values in intracurricular and extracurricular activities. Although there are several obstacles such as limited learning time and lack of support from the outside environment, teachers still try to shape students' positive attitudes towards democratic values, social responsibility, and respect for differences. Thus, the role of Civics teachers is very significant in shaping young citizens who have character and contribute to the life of the nation and state.